Parliamentary Elections in Latvia in the Year 2022 - Maluzinas, Martinas (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2022)
The present article covers parliamentary elections in the Republic of Latvia. An analysis of the conduct and institutional conditions of the 2022 parliamentary elections in Latvia is undertaken. Unlike the previous elections in 2018, there were no radical changes in Latvia. It was only two new parties with radical, populist, conservative, Eurosceptic and anti-systemic profiles with a right-wing orientation that managed to enter the Parliament. The party system remained moderately fragmented with a balance between the parties. A centre-right coalition formed the government and it is this coalition that the future government coalition will be formed around. The present analysis is based on a case study, which made it possible to look at a particular case and to draw conclusions about the conduct and outcome of the Latvian parliamentary elections.

Przedmiotem niniejszego artykułu są wybory parlamentarne w Republice Łotewskiej. Podjęto się analizy przebiegu i uwarunkowań instytucjonalnych wyborów parlamentarnych na Łotwie w 2022 r. W odróżnieniu do poprzednich wyborów w 2018 r. na Łotwie nie doszło do radykalnych zmian. Tylko dwóm nowym partiom o profilu radykalnym, populistycznym, konserwatywnym, eurosceptycznym i antysystemowym o identyfikacji prawicowej udało się wejść do parlamentu. System partyjny pozostał umiarkowanie rozdrobniony z równowagą pomiędzy partiami. Rząd utworzyła centroprawicowa koalicja i to wokół niej zostanie stworzona przyszła koalicja rządowa. Niniejszą analizę oparto na case study, co umożliwiło przyjrzeć się konkretnemu przypadkowi i wyciągnąć wnioski co do przebiegu i wyników wyborów parlamentarnych na Łotwie.
Wybory parlamentarne na Łotwie w 2022 roku
Keywords: parliamentary elections; party system; political parties; Latvia; wybory parlamentarne; system partyjny; partie polityczne; Łotwa